Interpretation of Diffusion Susceptibility Data Obtained with 50-μg Carbenicillin Discs Against Gram-Negative Organisms - Traub, Walter H. (1971)
A total of 284 clinical isolates of various species of Enterobacteriaceae, Pseudomonas aeruginosa, P. maltophilia, and Acinetobacter anitratum were tested for susceptibility to carbenicillin by the standardized Bauer-Kirby disc diffusion technique and a microtiter broth dilution method. The data obtained led to the following proposed criteria for the interpretation of the results of disc susceptibility tests. Enterobacteriaceae that yield zones of inhibition equal to or greater than 20 mm in diameter around 50-μg discs of carbenicillin are designated as sensitive to the drug; isolates that yield zones measuring from 18 to 19 mm in diameter are reported as of equivocal (intermediate) susceptibility to the drug, whereas those enterobacterial isolates that are characterized by zones of inhibition of 17 mm or less in diameter are interpreted as resistant to carbenicillin. Isolates of P. aeruginosa, P. maltophilia, and A. anitratum yielding zones of 14 mm or more in diameter around 50-μg discs of carbenicillin are reported as sensitive, whereas those isolates that are characterized by zones of 13 mm or less in diameter are reported as resistant to this drug.